Edukasi tentang Pencegahan dan Pengendalian Faktor Risiko Penyakit ‎Tidak Menular Di Wilayah Sungai Raya Dalam Kabupaten Kubu ‎Raya - Ariyanti, Sri; Surtikanti; Wahyuni, Tri; Kawuryan, Uji (TRIMAS: Jurnal Inovasi dan Pengabdian Kepada Masyarakat, 2023)
Non-communicable diseases are the leading causes of death in the world. The World Health Organization reports that 40 million people in the world suffer from non-communicable diseases in 2016. Non-communicable diseases have contributed to 73% of deaths in Indonesia where 26% occurred in adulthood. The purpose of this service is to increase public knowledge about the prevention control of risk factor non-communicable diseases. The method used  interactive lecture. The number of participants in this activity was 30 people who were vulnerable to non-communicable diseases. The results showed that there was an increase in knowledge about the prevention control of risk factor non-communicable diseases with the average difference in the pre-test 60 and post-test knowledge 75. Increasing public knowledge about efforts to prevent and control  non-communicable diseases risk factors can be realized by using appropriate education and creative methods so that people will more easily understand the material provided.